VD_FINDINFO HC / 2011 / 91 vom 25. November 2010 - VD Tribunal cantonal (2010)
RÉSILIATION IMMÉDIATE, JUSTE MOTIF, CONTRAT DE TRAVAIL | 337 al. 1 CO, 337 al. 2 CO, 337 al. 3 CO, 337 CO, 343 al. 3 CO, 46 LJT